A cross-sectional study of groceries shopping practices and body composition among adult consumers in Puncak Alam, Selangor / Nurhazimah Zakaria - Zakaria, Nurhazimah (2016)
In worldwide, prevalence of overweight and obesity is elevating tremendously. Obesity also has been associated as a threat and a leading cause of mortality in worldwide population including Malaysia. The objective of this study was to determine the association between groceries shopping practices and body composition status among adult consumers. A cross-sectional study was conducted among 118 subjects in Puncak Alam, Selangor. All individual who did groceries shopping at the hypermarket and aged within 20-64 years old were selected to participate in this study through a convenience sampling. A questionnaire session regarded on demographic data, socio-economic status, physical activity level and groceries shopping practices was conducted via face-to-face interview method. Anthropometric measurements in which covered on body weight, height and body mass index and waist circumference were obtained and recorded. This study showed that the prevalence of regular groceries shopping 56.8% (n=67) was higher than recommended shopping 43.2% (n=51). Data also showed that that majority of the subjects were overweight (24.68±4.72). In regard to waist circumference, majority of male was normal (87.82±9.99) whereas female had abdominal obesity (82.29±11.40). Moreover, this study illustrated that there was no significant correlations between both body mass index and waist circumference with groceries shopping score (p = 0.797, p = 0.725). In contrast, body mass index and waist circumference had significant correlations with physical activity level (p = 0.045, p = 0.009) both with negative poor correlation. Groceries shopping usually being performed to fulfil the household needed in which it served as household food availability. The availability of certain foods at home was associated in influencing the eating behaviour yet not fully represented the actual dietary intake. In conclusion, body composition status was not influence by the groceries shopping practices; regular or recommended indeed other factors such as physical activity and socioeconomic status. The findings of this study are useful to determine the high risk populations in which can be identified as potential target groups for nutrition and intervention programmes in order to combat the health inequity among adults.